On the Cranial Nerves - Hugo M. Libreros-Jiménez; Jorge Manzo; Fausto Rojas-Durán; Gonzalo E. Aranda-Abreu; Luis I. García-Hernández; Genaro A. Coria-Ávila; Deissy Herrera-Covarrubias; César A. Pérez-Estudillo; María Rebeca Toledo-Cárdenas; María Elena Hernández-Aguilar (NeuroSci, 2023)
The twelve cranial nerves play a crucial role in the nervous system, orchestrating a myriad of functions vital for our everyday life. These nerves are each specialized for particular tasks. Cranial nerve I, known as the olfactory nerve, is responsible for our sense of smell, allowing us to perceive and distinguish various scents. Cranial nerve II, or the optic nerve, is dedicated to vision, transmitting visual information from the eyes to the brain. Eye movements are governed by cranial nerves III, IV, and VI, ensuring our ability to track objects and focus. Cranial nerve V controls facial sensations and jaw movements, while cranial nerve VII, the facial nerve, facilitates facial expressions and taste perception. Cranial nerve VIII, or the vestibulocochlear nerve, plays a critical role in hearing and balance. Cranial nerve IX, the glossopharyngeal nerve, affects throat sensations and taste perception. Cranial nerve X, the vagus nerve, is a far-reaching nerve, influencing numerous internal organs, such as the heart, lungs, and digestive system. Cranial nerve XI, the accessory nerve, is responsible for neck muscle control, contributing to head movements. Finally, cranial nerve XII, the hypoglossal nerve, manages tongue movements, essential for speaking, swallowing, and breathing. Understanding these cranial nerves is fundamental in comprehending the intricate workings of our nervous system and the functions that sustain our daily lives.